Analisis Lingkungan Kontemporer Sebagai Sistem Nilai Manajemen dan Budaya Madrasah - Khotibul Umam (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2022)
Abstract This article discusses contemporary environmental analysis as a management value system and madrasa culture. Based on the results of data analysis, it can be concluded that the variables of the madrasa environment as a management value system and madrasa culture include: customers/markets, namely students (students) as the main customers; suppliers, intermediaries, public, economy, for example, average income or Gross domestic product, market tastes; demographics, politics, for example, the political policy of the national exam; laws, for example, the issuance of laws or regulations for BOS management; ecology, namely the school environment; technology, namely the acceleration of the use of high technology in learning; and socio-cultural, namely the values, attitudes, opinions and lifestyles of the people that influence the choice of educational institutions. Keywords; environmental analysis, management values, madrasa culture).